The Effect of the Lunar Cycle on Fecal Cortisol Metabolite Levels and Foraging Ecology of Nocturnally and Diurnally Active Spiny Mice - Gutman, Roee; Dayan, Tamar; Levy, Ofir; Schubert, Iris; Kronfeld-Schor, Noga (PLOS ONE, 2011)
We studied stress hormones and foraging of nocturnal Acomys cahirinus and diurnal A. russatus in field populations as well as in two field enclosures populated by both species and two field enclosures with individuals of A. russatus alone. When alone, A. russatus individuals become also nocturnally active. We asked whether nocturnally active A. russatus will respond to moon phase and whether this response will be obtained also in diurnally active individuals. We studied giving-up densities (GUDs) in artificial foraging patches and fecal cortisol metabolite levels. Both species exhibited elevated fecal cortisol metabolite levels and foraged to higher GUDs in full moon nights; thus A. russatus retains physiological response and behavioral patterns that correlate with full moon conditions, as can be expected in nocturnal rodents, in spite of its diurnal activity. The endocrinological and behavioral response of this diurnal species to moon phase reflects its evolutionary heritage.